Fetal Congenital Lobar Emphysema - Chun-Chieh Chia; Soon-Cen Huang; Min-Chang Liu; Tung-Yi Se (Elsevier, 2007)
Objective: To report a rare fetal congenital lung anomaly characterized by overinflation of a pulmonary lobe. Case Report: A 28-year-old systemic lupus erythematous mother, gravida 1 para 0, who had normal prenatal care in our department, was admitted for labor pain and an abnormal fetal heart location was noted incidentally during labor. The baby showed rib retraction in room air but no obvious cyanotic change after delivery. Both the fetus chest X-ray and ultrasound showed a hyperechogenic tumor in the left thoracic cavity with a right-side-shifted heart and trachea. Computed tomography showed a hypodense and multiseptal tumor in the left thoracic cavity with right-sided shift of the heart and trachea. It was a soft, solid tumor in the parenchyma of the left lung and the histopathology confirmed it to be benign congenital lobar emphysema. Conclusion: The favorable outcome in both asymptomatic and mildly symptomatic children suggests that a nonsurgical approach should be considered for these patients.